Reshaping the Future - Beard, Jill; Ball, David (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
A 5.3 million pounds sterling refurbishment and new build library project was undertaken by Bournemouth University. First inception to latest adaptation spans 2000–2008. The project gave equal weight to the refurbishment and new build and the building was opened in 2003. The philosophy was one of seeking a design that would allow adaptation and change. Winning the SCONUL building award 2007 is testament to the success of designing and implementing space and service delivery in a way that is sympathetic to developing pedagogy, student expectations and the University’s plans.